Modelling of Non-Stationary Regimes Along Multi-Line Linear Sections of the Pipeline - Гусарова, І. Г.; Полятикін, А. О. (KNPU, 2023)
The paper considers a mathematical model of non-stationary gas flow regimes on a multiline linear section of a gas pipeline. It consists of several parallel pipes of a given diameter with a common input and output.
Keywords: non-stationary non-isothermal regime of gas flow; multiline linear section of gas pipeline